Sistem Kepartaian di Madura Pasca Reformasi - Mohammad Fauzi (Jurnal Adhyasta Pemilu, 2022)
This article is a literature study with a descriptive-quantitative approach that discusses the party system in post-reform Madura. According to the results of the study, the party system in post-reform Madura in the last decade is an extreme multi-party system. Effective parties in the Regional House of Representative for the 2014-2019 period in Madura have an average of 8 parties and the Regional House of Representative for the 2019-2024 period have increased to 9 parties, while the fragmentation of the Regional House of Representative in the two periods have fragmented into 9 parties. The empirical data is shown by the average of the ENPP and Fragmentation Index of the Regional House of Representative for the two periods. The average ENPP Index of the Regional House of Representative for the 2014-2019 period was 8.41 and the Regional House of Representative for the 2019-2024 period increased to 8.54, while the Fragmentation Index of the Regional House of Representative for the 2014-2019 period was 0.88 and the Regional House of Representative for the 2019-2024 period increased to 0.89.